Secondary protective seal of root canal fillings performed under simulated clinical conditions - Johannes Ebert; Roland Frankenberger; Anselm Petschelt; Matthias Johannes Roggendorf (Revista Sul-Brasileira de Odontologia, 2012)
Objective: This study evaluated sealing properties of root canal fillings with an additional composite barrier. The null hypothesis tested was that different sealers and different methods of sealer removal did not influence microleakage. Material and methods: Eighty extracted human molars with fully mature apices had root canal prepared to size 60 taper .02 and divided into eight groups: three experimental groups for each sealer and negative/positive control (n = 10 each). Teeth of experimental groups were mounted into the molar region of a training puppet to simulate clinical conditions. Root canals were filled with AH Plus or GuttaFlow and gutta-percha. Excess sealer was removed with: ethanol-moistened foam pellet only, additional preparation with a water-cooled diamond bur or additional etch-and-rinse procedure (37% phosphoric acid gel). All procedures were carried out until clean as judged by the naked eye. In all groups except the positive control Syntac was applied to the access cavity. Tetric flow was applied in two increments of 1 mm each. A dye penetration test was carried out by centrifugation for 3 min at 30 G within 5% methylene blue dye. Statistical evaluation was carried out with PASW 18.0 (α = 0.05). Results: Although the two sealers had different chemical composition, sealer exhibited no influence on the results, whereas technique of sealer removal did (Two-way-ANOVA, p < 0.001). Groups with “foam pellet” or “bur preparation” showed significantly more leakage than groups with “etch-and rinse” (SNK, p < 0.05). Conclusion: Applying an etch-and-rinse procedure prior to Syntac may be beneficial for the adhesive seal over root canal fillings.